Maternal smoking during pregnancy and offspring smoking initiation: assessing the role of intrauterine exposure. - Taylor, Amy E.; Howe, Laura D.; Heron, Jon E.; Ware, Jennifer J.; Hickman, Matthew; Munafò, Marcus R. (Addiction, 2014)
Aims To assess whether associations between maternal smoking during pregnancy and offspring smoking initiation are due to intrauterine mechanisms. Design Comparison of associations of maternal and partner smoking behaviour during pregnancy with offspring smoking initiation using partner smoking as a negative control ( n = 6484) and a Mendelian randomization analysis ( n = 1020), using a genetic variant in the mothers as a proxy for smoking cessation during pregnancy. Setting A longitudinal birth cohort in South West England. Participants Participants of the Avon Longitudinal Study of Parents and Children ( ALSPAC). Measurements Smoking status during pregnancy was self-reported by mother and partner in questionnaires administered at pregnancy. Latent classes of offspring smoking initiation (non-smokers, experimenters, late-onset regular smokers and early-onset regular smokers) were previously developed from questionnaires administered at 14-16 years. A genetic variant, rs1051730, was genotyped in the mothers. Findings Both mother and partner smoking were similarly positively associated with offspring smoking initiation classes, even after adjustment for confounders. Odds ratios (OR) [95% confidence interval ( CI)] for class membership compared with non-smokers were: experimenters: mother OR = 1.33 (95% CI = 1.06, 1.67), partner OR = 1.28 (95% CI = 1.06, 1.55), late-onset regular smokers: mother OR = 1.80 (95% CI = 1.43, 2.26), partner OR = 1.86 (95% CI = 1.52, 2.28) and early-onset regular smokers: mother OR = 2.89 (95% CI = 2.12, 3.94), partner OR = 2.50 (95% CI = 1.85, 3.37). There was no clear evidence for a dose-response effect of either mother or partner smoking heaviness on class membership. Maternal rs1051730 genotype was not clearly associated with offspring smoking initiation class in pre-pregnancy smokers ( P = 0.35). Conclusion The association between smoking during pregnancy and offspring smoking initiation does not appear to operate through intrauterine mechanisms.